Padrão de descrição de informação: avaliação da capacidade representacional de bens materiais - Almeida, Milene Rosa de (2014)
The rural development in the Brazilian South and Southeast started in the mid-eighteenth century, initially by mining and later by coffee and sugar cane crops. Besides the economic development, the architecture and culture are highlights from these regions. In order to describe tangible and intangible rural heritage from these farms, it was developed the Information Description Standard (IDS) using theoretical and methodological Information and computer sciences precepts. The IDS is compound by 13 description groups according to the scope, content and kind of heritage assets. The parameters to obtain a completed and detailed description of the heritage assets were taken from codes, standards and librarianship, archival, museological and computer science roadmaps. This research conducted a comparative study between the IDS description fields and the standard Machine Readable Cataloging (MARC 21), widely used in libraries. The methodology used a theoretical study on rural heritage and cataloging, highlighting the MARC 21 standard, followed by the comparative analysis of IDS and MARC 21. As a result, it was pointed out that the IDS needs of small interventions to enable a more complete description of the properties identified in São Paulo historic farms. In the end, it was concluded that IDS is able to perform the descriptive representation of the rural heritage satisfactorily.